Impact of the activity of federal executive branches on ensuring national security of Russia in the Arctic Region - Kuzmenko, Artem Olegovich (Вопросы безопасности, 2020)
The subject of this research is national interests of the Russian Federation in the Arctic region. Russia's national interests in the Arctic are versatile and quite complex, representing an intersection of the spheres of national interests of Russia as a whole and such particular vectors as the World Ocean, economic sphere, border zone, etc. They are delineated with different degree of specification in a range of normative legal and other documents. Systematization of national interests, factors and threats in the Arctic zone, as well as understanding of their interrelation is an important step in ensuring national security of Russia in the Arctic Region. The analysis of normative legal acts allows systematizing the factors influencing the activity of federal executive branches in the Arctic, as well as outlining the threats to national security of Russia in the Arctic Region. The author analyzes correlation between the factors and threats to Russia's national interests and the vectors of activity of the federal executive branches on their neutralization. Such approach towards interdependence of factors, interests, and vectors of activity is of comprehensive, which discerns it from other existing approaches. The parallel is drawn between the indicated correlation and the dual layer neural network. The author assesses the feasibility of the proposed original approach for estimating the impact of activity of the federal executive branches on ensuring national interests, and offers relevant recommendations.